Does Postoperative Spine Infection Bacterial Gram Type Affect Surgical Debridement or Antibiotic Duration?. Issue 21 (1st November 2022) - Karamian, Brian A.; Lambrechts, Mark J.; Sirch, Francis; Gupta, Sachin; D'Antonio, Nicholas D.; Levy, Hannah; Reiter, David; Dolhse, Nico; Qureshi, Mahir; Mao, Jennifer; Canseco, Jose A.; Woods, Barrett I.; et al.
Abstract : Study Design: This is a retrospective cohort study. Objective: The aim was to evaluate differences in readmission rates, number of debridements, and length of antibiotic therapy when comparing bacterial gram type following lumbar spinal fusion infections. Summary of Background Data: Surgical site infections (SSIs) after spinal fusion serve as a significant source of patient morbidity. It remains to be elucidated how bacterial classification of the infecting organism affects the management of postoperative spinal SSI. Methods: Patients who underwent spinal fusion with a subsequent diagnosis of SSI between 2013 and 2019 were retrospectively identified. Patients were grouped based on bacterial infection type (gram-positive, gram-negative, or mixed infections). Poisson regressions analyzed the relationship between the type of bacterial infection and the number of irrigation and debridement (I&D) reoperations, and the duration of intravenous (IV) antibiotic therapy. Significance was set at P <0.05 Results: Of 190 patients, 92 had gram-positive (G+) infections, 57 had gram-negative (G−) infections, and 33 had mixed (M) infections. There was no difference in 30 or 90-day readmissions for infection between groups (both P =0.051). Patients in the M group had longer durations of IV antibiotic treatment (G+: 46.4 vs. G−: 41.0 vs. M: 55.9 d, P =0.002). Regression analysis demonstrated mixed infections were 46% more likely to require a greater number of debridements ( P =0.001) and 18% more likely to require an increased duration of IV antibiotic therapy ( P <0.001), while gram-negative infections were 10% less likely to require an increased duration of IV antibiotic therapy ( P <0.001) when compared with G− infections. Conclusion: Spinal SSI due to a mixed bacterial gram type results in an increased number of debridements and a longer duration of IV antibiotics required to resolve the infection compared with gram-negative or gram-positive infections. Level of Evidence: Level III.